2008
DOI: 10.1016/j.ejc.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Steiner distance and convexity in graphs

Abstract: We use the Steiner distance to define a convexity in the vertex set of a graph, which has a nice behavior in the well-known class of HHD-free graphs. For this graph class, we prove that any Steiner tree of a vertex set is included into the geodesical convex hull of the set, which extends the well-known fact that the Euclidean convex hull contains at least one Steiner tree for any planar point set. We also characterize the graph class where Steiner convexity becomes a convex geometry, and provide a vertex set t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 11 publications
0
30
0
1
Order By: Relevance
“…In a similar way, totally balanced hypergraphs and strongly chordal graphs have been characterized as convex geometries of some particular (hyper)graph convexities [16]. More recently, the so-called Steiner convexity was introduced, and it was shown that precisely 3-fan-free chordal graphs are convex geometries with respect to this convexity [6].…”
Section: Introductionmentioning
confidence: 97%
“…In a similar way, totally balanced hypergraphs and strongly chordal graphs have been characterized as convex geometries of some particular (hyper)graph convexities [16]. More recently, the so-called Steiner convexity was introduced, and it was shown that precisely 3-fan-free chordal graphs are convex geometries with respect to this convexity [6].…”
Section: Introductionmentioning
confidence: 97%
“…Further results involving Steiner tree problems related to geodesic convexity in graphs can be found in [15,18,26,28,47,55,96,115,116,136,150,152,155,172,180].…”
Section: Theorem 512 ([119]) Every Edge Steiner Set Of a Connected mentioning
confidence: 99%
“…While several convexity notions exist for graphs (e.g., g-convexity [7], m-convexity [5,7], ap-convexity [4], tpconvexity [3], Steiner convexity [2,10]), fewer convexity notions have been defined explicitly for hypergraphs. The first hypergraph convexity that has been introduced is simple-path convexity (sp-convexity, for short) [7], which is a generalization of ap-convexity.…”
Section: Introductionmentioning
confidence: 99%